Analisis Pemasaran Gabah di Kecamatan Kubu Kabupaten Rokan Hilir - Awaluddin Awaluddin; Ahmad Rifai; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to: (1) Know the channel and function of rice marketing in Kubu Rokan Hilir District. (2) Analyze cost, margin, and efficiency of rice marketing in Kubu sub district Rokan Hilir District. This research was conducted by survey method with the help of quisioner to interact with sample and sampling take  20 samples of farmers and buyers of rice. Data analysis using Snowball Sampling. The results showed that the rice marketing channel in Kubu sub-district only had one marketing channel from farmers to big traders to RMU (Tebing Tinggi). The function of rice marketing in Kubu Sub-district was done by marketing institutions such as farmers, Collecting traders, Big trader and RMU Tebing Tinggi which includes the functions of exchange, physical function and facility function. At farmers the cost does not incur marketing expenses. In the merchant collecting the marketing expenses incurred is the transportation cost of Rp 200 / kg which is the cost for transportation. While the big trader spend on loading and unloading marketing costs of Rp 85 / kg, transportation costs of Rp 200 / kg and total marketing costs Rp 485 / kg. While the marketing efficiency is 9.89% and the marketing profit is Rp 640 / kg and the share received by farmers is 77.26%.Keywords: Marketing, Rice, margin, efficiency and cost.